The Equity Market Reaction to Corporate Climate Action Bond Issue Announcements - Chetty, Tarah (Department of Finance and Tax, 2024)
Climate change has become the defining crisis of our time. Without drastic action today, adapting to the future impact of this issue will be both challenging and costly. Green bonds enable capital-raising and investment for projects that have a positive impact on the environment, facilitating the mobilisation of financial resources for projects to combat climate change. This study is the first to adopt a United Nations Sustainable Development Goals lens, specifically focusing on SDG 13: Climate action, to investigate the market reaction to a global sample of 276 corporate climate action bond issue announcements between the inception of the green bond market in 2007 and 2022. Firstly, an event study is conducted to assess the equity market's reaction to corporate climate action bond issue announcements, and secondly, a regression is used to investigate possible factors correlated with the magnitude of the market reaction both on the bond announcement date, as well as over ten days thereafter. The factors tested against cumulative excess returns in the second part of the study are the size of the bond relative to the size of the issuer, first time issuance vs subsequent issuances, the issuing company's ESG, environmental, and governance disclosure scores, the profitability of the issuing firm and the Environmental Performance Score (EPI). The study finds that green bonds yield positive announcement returns on the announcement day, but that cumulative abnormal equity returns follow a downward trend over the subsequent 10 days. Further, the size of the bond relative to the size of the issuer is found to be statistically significantly correlated with the announcement day abnormal return, whilst the profitability of the issuing firm and whether the issue is the first climate change bond issued by a company or a subsequent issuance, are found to be correlated with some statistical significance to the ten-day cumulative abnormal returns. Thus, post-announcement the shares of companies announcing green bond issues underperform on a risk-adjusted basis, which could indicate that on average the market is not convinced that the proceeds of these green bonds will be well used. Thus, they may not be effective in closing environmental investment gaps as is intended, which could indicate that the issuers of these bonds have to do more work to convince the market of their use.